Signs of learning in middle school computing education - Kjallander, Susanne; Akerfeldt, Anna; Mannila, Linda; Heintz, Fredrik (Proceedings - Frontiers in Education Conference, 2022)
Programming has been part of Swedish elementary school curriculum for six years and the aim of this full paper is to find out how teachers can design programming activities so that students engage and learn. A mix-methods research project with a social semiotic, multimodal theoretical framework - Designs for learning - is used to investigate teaching and learning in a class during three years. The results in this small-scale study indicate that collaboration is a successful didactic design for programming lessons in school. Computational thinking is prevalent and both digital skills (such as coding) and digital competencies (such as understanding the impact of technology in society) are practiced and met in programming lessons merging Science, Technology, Engineering, Arts, and Mathematics.